Operative versus Non-Operative Management of Traumatic Thoracolumbar Injuries according to the AO Spine Thoracolumbar Spine Injury Classification System - Joaquim, Andrei F. (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Introduction The AOSpine Thoracolumbar Spine Injury Classification (AOSTSIC) system has been proposed to better characterize injury morphologies and improve the classification of thoracolumbar (TL) spine trauma. However, the indications for surgical treatment according to the AOSTSIC system are still debated. Additionally, the proposed Thoracolumbar AOSpine Injury Score (AOSIS) is quite complex, which may preclude its use in daily practice. The objective of this review is to discuss the AOSTSIC system and its indications for initial nonoperative versus surgical management of acute TL spine trauma.Methods We analyzed the literature for each injury type (and subtype, when pertinent) according to the AOSTSIC system as well as their potential treatment options.Results Patients with AOSTSIC subtypes A0, A1, and A2 are neurologically intact in the vast majority of the cases and initially managed nonoperatively. The treatment of A3- and A4-subtype injuries (burst fractures) in neurologically-intact patients is still debated with great controversy, with initially nonoperative management being considered an option in select patients. Surgery is recommended when there are neurological deficits or failure of nonoperative management, with the role of magnetic resonance findings in the Posterior Ligamentous Complex (PLC) evaluation still being considered controversial. Injuries classified as type B1 in neurologically-intact patients may be treated, initially, with nonoperative management, provided that there are no ligamentous injury and non-displacing fragments. Due to severe ligamentous injury, type-B and type-C injuries should be considered as unstable injuries that must be surgically treated, regardless of the neurological status of the patient.Conclusions Until further evidence, we provided an easy algorithm-based guide on the spinal trauma literature to help surgeons in the decision-making process for the treatment of TL spine injuries classified according to the new AOSTSIC system.
Keywords: AOSpine; thoracolumbar; surgery; non-operative; classification; treatment; fracture